Properties of 3D Double-Arrow Negative Poisson’s Ratio Lattice Structure under Quasi-Static Compression and Low-Speed Impact - Fuzhen Sun; Meng Liu; Baoming Wang; Na Yang; Jianfeng Wang; Keqian Cai; Zizhi Liu (Advances in Materials Science and Engineering)
Structures with negative Poisson’s ratios have wide applications in automotive design, owing to their excellent mechanical properties and good energy absorption capability. This type of structure can be used to design lightweight components. We used a double-arrow negative Poisson ratio structure and embedded lock assembly process to design a 3D lattice structure with a negative Poisson ratio. Moreover, we selected different design parameters for a simulation analysis and experimental research. The performances of the lattice structures with different parameters were compared and analyzed under different test conditions, including out-of-plane compression, three-point bending, and low-speed impact. The findings reported here pave the way for the development of new 3D auxetic materials with significantly expanded design space and potential applications by reducing the difficulty of the manufacturing process.